International norms and the politics of sexuality education in Nigeria - Jeremy Shiffman; Michael Kunnuji; Yusra Ribhi Shawar; Rachel Sullivan Robinson (BMC, 2018)
Abstract Background Proponents have promoted sexuality education as a means of empowering adolescents, yet it has been thwarted in many low and middle-income countries. Nigeria represents an exception. Despite social opposition, the government in 1999 unexpectedly approved sexuality education policy. Since then, implementation has advanced, although efficacy has differed across states. We draw on theory concerning international norm diffusion to understand Nigerian policy development. Results We find that a confluence of international and national norms and interests shaped policy outcomes, including concern over HIV/AIDS. A central dynamic was an alliance of domestic NGOs and international donors pressing the Nigerian government to act. Conclusions We argue that theory on international norms can be applied to understand policy dynamics across a variety of health and population areas, finding value in approaches that integrate rather than juxtapose consideration of (1) international and national influences; (2) long and short-term perspectives on policy change; and (3) norms and interests.